2013
DOI: 10.2478/s13382-013-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response to acute exposure to welding fumes during the working day

Abstract: Objectives: To investigate cardiorespiratory and inflammatory responses in male workers following exposure to welding fumes and airborne particles in actual workplace conditions. Materials and Methods: We measured blood leukocytes and their differential counts, platelet count, hemoglobin, sensitive C-reactive protein, fibrinogen, E-selectin, IL-(interleukin)1β, IL-6, IL-8, tumor necrosis factor alpha (TNF-α) and endothelin-1 in blood samples of twenty workers before and after their working day. We also studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 46 publications
(70 reference statements)
10
23
1
Order By: Relevance
“…Kauppi et al (Kauppi et al, 2015) analyzed platelet counts, leucocytes and their differential counts, hemoglobin, sensitive C reactive protein (CRP), lipids, glucose and fibrinogen, interleukins IL-1β, IL-6, IL-8, TNF-α, endothelin-1, and E-selectin in plasma samples collected from 16 welders with suspected occupational asthma. Based on the observed increased level of blood leukocytes, neutrophils, and platelets, and the decreased level of hemoglobin and erythrocytes, they concluded that a mild systemic inflammatory response takes place during welding exposure, in line with the results of earlier studies (Jarvela et al, 2013;Kim et al, 2005;Scharrer et al, 2007). However, they observed no statistical difference whether in CRP or in acute-phase mediators IL-6, IL-8, and TNF-α, while pro-inflammatory cytokine IL-1β and E-selectin levels decreased significantly.…”
Section: Studies Of Nanoparticulate Components Of Welding Fumes and Tsupporting
confidence: 82%
See 2 more Smart Citations
“…Kauppi et al (Kauppi et al, 2015) analyzed platelet counts, leucocytes and their differential counts, hemoglobin, sensitive C reactive protein (CRP), lipids, glucose and fibrinogen, interleukins IL-1β, IL-6, IL-8, TNF-α, endothelin-1, and E-selectin in plasma samples collected from 16 welders with suspected occupational asthma. Based on the observed increased level of blood leukocytes, neutrophils, and platelets, and the decreased level of hemoglobin and erythrocytes, they concluded that a mild systemic inflammatory response takes place during welding exposure, in line with the results of earlier studies (Jarvela et al, 2013;Kim et al, 2005;Scharrer et al, 2007). However, they observed no statistical difference whether in CRP or in acute-phase mediators IL-6, IL-8, and TNF-α, while pro-inflammatory cytokine IL-1β and E-selectin levels decreased significantly.…”
Section: Studies Of Nanoparticulate Components Of Welding Fumes and Tsupporting
confidence: 82%
“…However, they observed no statistical difference whether in CRP or in acute-phase mediators IL-6, IL-8, and TNF-α, while pro-inflammatory cytokine IL-1β and E-selectin levels decreased significantly. Although no study allows comparison with the latter finding, existing studies on CRP are still contradictory: Kim et al (2005) (Kim et al, 2005) support significant CRP changes related to welding fume exposure, while Brand et al (2014), Järvelä et al (2013, and Scharrer et al (2007), (Brand et al, 2014;Jarvela et al, 2013;Scharrer et al, 2007) do not. Very recently, Grazcyk et al (Graczyk et al, 2016b) collected exhaled breath condensate, blood and urine from 20 non-smoking male welding apprentices at different time points: 1)-before exposure, 2)-immediately after exposure, 3)-one hour after exposure, and 4)-three hours after exposure to assess oxidative stress biomarker concentrations (8-hydroxy-2'-deoxyguanosine, malondialdehyde, hydrogen peroxide, and total reducing capacity) at each time point.…”
Section: Studies Of Nanoparticulate Components Of Welding Fumes and Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Exposures to different particle sizes have different effects on human morbidity and mortality. Increased mortality rates have been associated with PM 2.5 and PM 10 (Dockery et al 1993; Landen et al 2011; Ostro et al 2015; Zanobetti and Schwartz 2009), lung cancer with PM 2.5 (Harrison et al 2004; Pope et al 2002), and cardiopulmonary diseases with PM 1 , PM 2.5 , and PM 10 (Burnett et al 1999; Franck et al 2011; Järvelä et al 2013; Ostro et al 2015; Polichetti et al 2009). Environmental studies show that PM 2.5 from combustion sources are more strongly associated with mortality (Schwartz et al 1996) and adverse respiratory health effects (Schwartz and Neas 2000) than coarse particles (PM 10-2.5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Welding is another profession wherein workers are exposed to higher amounts of air pollution [119]. However, Jarvela et al [120] determined that an 8-h dust and welding fume exposure (inhalable dust; 1.5–35 mg/m 3 ) did not significantly change the workers’ levels of plasma ET-1, yet exposure to welding fumes (alveolar particle fraction; 1.0–25.3 mg/m 3 ) significantly decreased ET-1 [121]. The investigators hypothesized that this contradictory response could be due to the heterogeneous mix of the welding fumes, which included high levels of nitrogen oxides that could disrupt the homeostasis in the vasculature.…”
Section: Introductionmentioning
confidence: 99%